Early-planted soybean weed management as affected by herbicide application rate and timing - Logan R. Miller; Christopher A. Landau; Martin M. Williams; Aaron G. Hager (Weed Technology)
The opportunity to increase soybean yield has prompted Illinois farmers to plant soybean earlier than historical norms. Extending the growing season with an earlier planting date might alter the relationship between soybean growth and weed emergence timings, potentially altering the optimal herbicide application timings to minimize crop yield loss due to weed interference and ensure minimal weed seed production. The objective of this research was to examine various herbicide treatments applied at different timings and rates to assess the effect on weed control and yield in early-planted soybean. Field experiments were conducted in 2021 at three locations across central Illinois to determine effective chemical strategies for weed management in early-planted soybean. PRE treatments consisted of a S-metolachlor + metribuzin premix applied at planting or just prior to soybean emergence at 0.5X (883 + 210 g ai ha−1) or 1X (1,766 + 420 g ai ha−1) label-recommended rates. POST treatments were applied when weeds reached 10 cm tall and consisted of 1X rates of glufosinate (655 g ai ha−1) + glyphosate (1,260 g ae ha−1) + ammonium sulfate, without or with pyroxasulfone at a 0.5X (63 g ai ha−1) or 1X (126 g ai ha−1) rate. Treatments comprising both a full rate of PRE followed by a POST resulted in the greatest and most consistent weed control at the final evaluation timing. The addition of pyroxasulfone to POST treatments did not consistently reduce late-season weed emergence. The lack of a consistent effect by pyroxasulfone could be attributed to suppression of weeds by soybean canopy closure due to earlier soybean development. The full rate of PRE extended the timing of POST application 2 to 3 wk for all treatments at all locations except Urbana. Full-rate PRE treatments also reduced the time between the POST application and soybean canopy closure. Overall, a full-rate PRE reduced early-season weed interference and minimized soybean yield loss due to weed interference.